(untitled) (Encuentros, 2021)
The results of an exercise in documentary analysis of the concept of pedagogical innovation are presented through the tracking of documents in databases in the period 2000-2018 where coding actions were developed from the proposal of the grounded theory that allowed generating a mapping of the characteristics of the concept of pedagogical innovation in academic production. There is a broad understanding of the concept, as well as the relational elements to it, which are consolidated as necessary action points for the consolidation of processes that point to the transformation of the institutional culture, particularly in the dimension of knowledge and pedagogical practices. This article aims to delineate these components from the conceptual, epistemological and methodological dimension, as well as give some recommendations for the implementation of pedagogical innovation processes.